9 The Statutes at Large of South Carolina: Containing the Acts Relating to Roads, Bridges and Ferries, With an Appendix, Containing the Militia Acts Prior to 1794, at 645-47 (David J. McCord ed., 1841) - (:unkn) unknown (My University, 1747)
Affirmed that it was "lawful to . . . call together all male persons in this Province, from the age of sixteen to sixty years." It also made "every person liable to appear and bear arms . . . keep in his house, or at his usual place of residence, and bring with him to such muster, exercise or training, one gun or musket, fit for service, a cover for his lock, one cartridge box," twelve cartridges, horn or flask filled with at least a quarter pound of gun powder, a shot pouch with appropriate bullets, "one girdle or belt, one ball of wax . . . to defend his arms in rain, one worm and picker, four spare flints, a bayonet, sword or hatchet.
Keywords: MILITIAS; REQUIRED POSSESSION